Overcoming recruitment barriers through meaningful community engagement: lessons learned from a maternal-child food insecurity assessment in underserved communities - Buccini, Gabriela; Hernandez, Cristina; Herlosky, Kristen N.; Rabb, Shannon; Guillen, Lizette; Simangan, Dodds; Desai, Jyoti; Brown, Alison; Chinn, Juanita; Grigsby, Timothy; Flatt, Jason; Baumann, Ana A. (Frontiers in Public Health, 2025)
BackgroundRecruiting participants from underserved communities for research can be challenging due to multilevel barriers. We conducted a maternal-child food insecurity needs assessment within underserved communities in urban Las Vegas, Nevada, and numerous barriers were faced to recruiting participants. This study aimed to examine barriers to participant recruitment, identify practical strategies for engaging participants, and analyze these strategies guided by the Meaningful Community Engagement Framework.MethodsThis case study used an ethnography approach to analyze data collection barriers and community engagement strategies employed from March 2022 to February 2023 during a maternal-child food insecurity needs assessment. Inductive and deductive qualitative coding was used to classify barriers across three socio-ecological levels (families, service, and community). Engagement strategies were mapped onto the five principles of the Meaningful Community Engagement Framework guided by social justice, equity, and trust building.ResultsEleven barriers to participant recruitment were identified. At the community level, a history of being over-surveyed created apathy toward the maternal-child food insecurity needs assessment. At the service level, overburdened clinical staff were unwilling to participate in our survey. At the family level, participants questioned the legitimacy of advertising materials, length of the survey, low incentive amount, and were fearful of connection with state or federal programs and mandated reporting. To address the recruitment barriers, fifteen practical engagement strategies were mapped out across principles of the Meaningful Community Engagement Framework: “Building trust and long-term relationships” (n = 4), “Listening with a blank slate” (n = 3), “Planning to compensate for contributions” (n = 3), “Community service with no strings attached” (n = 3), “Focus on capacity building” (n = 2).ConclusionBarriers to participant recruitment emerged across families, service, and community levels, highlighting the systemic challenges to research participation within underserved populations. The successful use of practical engagement strategies leveraged the connection with trusted community organizations and individuals, securing the successful completion of the maternal-child food insecurity needs assessment.